2006
DOI: 10.1371/journal.pmed.0030327
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of CSF: Evidence That Early Intervention May Impact on Disease Progression and Outcome in Schizophrenia

Abstract: BackgroundThe identification of schizophrenia biomarkers is a crucial step towards improving current diagnosis, developing new presymptomatic treatments, identifying high-risk individuals and disease subgroups, and assessing the efficacy of preventative interventions at a rate that is not currently possible.Methods and Findings 1H nuclear magnetic resonance spectroscopy in conjunction with computerized pattern recognition analysis were employed to investigate metabolic profiles of a total of 152 cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
169
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(180 citation statements)
references
References 41 publications
6
169
1
4
Order By: Relevance
“…34,35 A deeper understanding of global perturbations in biochemical pathways in complex diseases such as schizophrenia and upon treatment with antipsychotics could provide valuable insights about mechanisms of disease, drug effects and biomarkers. 35 Holmes et al 36 used an NMR-based metabolomics platform to evaluate a subset of pathways implicated in intermediary metabolism and established that glucose and acetate were modified in cerebrospinal fluid of patients with schizophrenia. The findings reported here represent to our knowledge, a first attempt to map global lipid changes in schizophrenia before and after treatment with three antipsychotics using a specialized metabolomics platform referred to as lipidomics.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 A deeper understanding of global perturbations in biochemical pathways in complex diseases such as schizophrenia and upon treatment with antipsychotics could provide valuable insights about mechanisms of disease, drug effects and biomarkers. 35 Holmes et al 36 used an NMR-based metabolomics platform to evaluate a subset of pathways implicated in intermediary metabolism and established that glucose and acetate were modified in cerebrospinal fluid of patients with schizophrenia. The findings reported here represent to our knowledge, a first attempt to map global lipid changes in schizophrenia before and after treatment with three antipsychotics using a specialized metabolomics platform referred to as lipidomics.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR spectroscopy-based metabonomic analysis can be used to monitor a wide range of metabolites in biological samples, allowing for a sensitive, highthroughput molecular screening. [13][14][15] NMR spectroscopy is methodologically similar to in vivo MRS, but enables higher resolution of spectra for more accurate quantitation and greater sensitivity, allowing the detection of less abundant metabolites. Although there are many platforms for metabolic profiling (for example, LC-MS, GC-MS, NMR, electrocapillary phoresis-MS), no one technology gives complete coverage of the metabonome.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many platforms for metabolic profiling (for example, LC-MS, GC-MS, NMR, electrocapillary phoresis-MS), no one technology gives complete coverage of the metabonome. This technique has been used extensively in studies on schizophrenia, [16][17][18][19] Alzheimer's disease, 20 Huntington's disease, 21 Batten disease 22 and human brain tumors 23 (for detailed reviews on metabonomics, see Holmes et al 24 and Lenz and Wilson 25 ). These studies have identified a number of biochemical alterations that may be occurring as part of the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found altered expression of metabolic genes and altered levels of metabolites in the cerebrospinal fluid of live patients with schizophrenia (Holmes et al 2006, Huang et al 2007 and in the postmortem brain tissues of schizophrenia patients (Altar et al 2005;Prabakaran et al 2004;Prabakaran et al 2007). One of the postmortem studies reported altered transcription of genes in a large number of metabolic pathways and increased lactate levels in the prefrontal cortex (PFC) of patients with schizophrenia (Prabakaran et al 2004).…”
Section: Introductionmentioning
confidence: 99%